The function of MYC in youth development in Malaysia - Abdullah, Haslinda; Md Nor, Siti Maryam; Dahalan, Dzulhailmi; Hamzah, Azimi; Krauss, Steven Eric; Ismail, Ismi Arif; Tamam, Ezhar; Suandi, Turiman; Ahmad, Nobaya; Gill, Sarjit S. (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
In Malaysia, youth is defined as anyone who is between 15 and 40 years old. From this age interval are significant in terms of numbers and if translated into a source of energy, youth give positive influence to the nation development in term of the political (the voters), social (cohesion) and economic (human capital) aspects. Malaysian Youth Council (MYC) is a recognized non-governmental organization that represents the voice of Malaysian youth. The objective of the establishment of youth organizations in Malaysia is to provide tools and opportunities for youth development, empowerment and engagement so that young people can contribute towards national building. MYC has three main functions: 1) to implement youth development, 2) to coordinate and organizes activity, service and advocacy, and 3) to serve as a platform for youth delegates in a variety of scope and level. Since the majority of Malaysian population is under 40 years old, the continuing youth development programs and initiatives should involve youth directly. The objective of the present study was to evaluate the effectiveness of MYC in youth development in Malaysia. The results indicate that the Malaysian youth Council (MYC) needs the supports of community members and affiliates to be effective in achieving its goals.